Implementation Of Website-Based E-Counseling KOCAS (Student Confession Box) As A Medium For Disclosing Student Problems - Magfiratul Hidayah; Nurhikmah H; Rina Asriani Bakri; M. Fiqri Syahril (Universitas Negeri Medan, 2025)
This research examines the implementation of Website-Based E-Counseling KOCAS (Student Complaint Box) as a Media for Disclosing Student Problems in Schools. Guidance and counseling teachers can use media to help provide services to students. One of them is with a problem box, both physical and digital, which can provide students with a space to express problems without fear, helping counselors understand and handle problems proactively. Guidance and counseling have a very important role in the academic, social and emotional development of students, but there are still many negative stigmas attached to BK services in schools, especially at SMAN 1 Bulukumba. This study aims to analyze the implementation of E-Counseling Student Complaint Box (KOCAS) as a digital instrument in supporting more efficient service transformation and changing negative perspectives and stigmas as well as the limited implementation of guidance and counseling services for students in schools. The type of research is development research with data collection techniques used are interviews and questionnaires. The results of the study indicate that the website-based e-counseling system KOCAS (Student Confession Box) as a medium for students to express their problems at school has shown positive responses and is acceptable. A small group trial of 10 students with a counselor showed very positive (high) responses and is therefore acceptable. These findings indicate that the e-counseling system KOCAS is effective in helping students express emotions, uncover problems, strengthen the relationship between counselors and students, and eliminate the negative stigma surrounding guidance and counseling services.